Policy Review: Childlike Joy – Participation and Perspectives on the Arts of Irish Youth - Neil, Eleanor (Irish Journal of Arts Management and Cultural Policy, 2025)
This review examines the impact of arts and cultural participation on the well-being of Irish youth, focusing on three key reports: The Arts Council/An Chomhairle Ealaíon Report on Children, Young People and the Arts; Engagement in culture, arts, heritage and sport by young people in Northern Ireland: Findings from the Young Persons’ Behaviour and Attitudes Survey 2022; and the Arts Council of Northern Ireland’s Creative Schools Partnership Evaluation Report 2022. These documents highlight the diverse ways in which arts engagement enhances the lives of young people, and how children and young people perceive the role of the arts in their lives. The findings all confirm the necessity of integrating young voices into policy frameworks and the power of community-driven arts and culture initiatives, and the need for sustained support and innovation in nurturing arts and culture for the next generation.